Taxonomic diversity and ethnobotanical importance of adventive medicinal plants in the urban flora of Andijan city (Uzbekistan) - Sidikjanov, N.M.; Bussmann, Rainer W.; Kosimov, Zokir; Rahmonov, N.R.; Esanqulova, D.S.; Ruzimatov, R.Y.; Avalbayev, O.N.; Nasimova, Z.H.; Kaypov, K.P.; Xudoyberdieava, G.S.; Nazarov, N.B.; Khujanov, A.N.; et al. (Ethnobotany Research and Applications, 2026)
Background: Urban ecosystems are characterized by intensive anthropogenic transformation that facilitates the spread of adventive plant species. Many of these species possess medicinal properties and are widely used in traditional ethnobotanical practices. However, the taxonomic diversity and ethnobotanical importance of adventive medicinal plants in urban flora remain insufficiently studied in many regions, including Uzbekistan. Methods: Floristic surveys were conducted in different urban habitats of Andijan city (Uzbekistan) during the vegetation seasons of 2019–2023 using route (transect) methods. Plant identification was carried out based on regional floristic literature and herbarium materials. Ethnobotanical information on medicinal plant use was compiled from published scientific and ethnobotanical sources. Results: A total of 66 medicinal plant species belonging to 61 genera and 22 families were recorded in the urban flora of Andijan city. The taxonomic spectrum showed that the majority of species belong to the families Asteraceae, Fabaceae, Brassicaceae, Lamiaceae, and Polygonaceae, which represent the dominant medicinal plant groups in the urban environment. Ethnobotanical analysis revealed that many species are traditionally used for treating digestive, respiratory, inflammatory, and skin-related diseases. However, medicinal plants growing in urban environments may accumulate heavy metals and other anthropogenic pollutants originating from transport emissions, industrial activities and contaminated soils. Therefore, the safety of medicinal plants collected from urban habitats should be carefully evaluated before their use in traditional medicine. Conclusions: The results highlight the ecological and ethnobotanical importance of adventive medicinal plants as a significant component of urban biodiversity. The findings contribute to a better understanding of the role of adventive species in urban ecosystems and emphasize the need to consider ecological safety when using medicinal plants collected from urban environments. Keywords: Alien plants; Urban ecosystems; Traditional medicine; Floristic diversity; Anthropogenic habitats; Uzbekistan